Characterization of Secondary Metabolites Profile from Methanol Fraction of Temurui (Murraya koenigii (Linn.) Spreng) Leaves Using UPLC-MS - Intania Permata; Adlis Santoni; Afrizal Afrizal; Trisno Afandi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
The leaves of the temurui (Murraya koenigii (Linn.) Spreng) plant have long been known and used by Indonesian and even Asian people as a traditional medicine to treat stomach aches and diabetes. This study aimed to determine the secondary metabolite profile of the methanol extract of M. koenigii leaves. Murraya koenigii leaves fine powder was extracted in stages using n-hexane, ethyl acetate, and methanol. Each extract was prepared using a mixture of water, formic acid, acetonitrile, and formic acid, then injected into the UPLC-MS, then analyzed with MassLynx and ChemSpider. The results showed that the metabolite profile of the methanol extract of M. koenigii leaves contained 13 compounds, including phenolic, steroid, and alkaloid groups. Those compounds could be tested to identify their bioactivity.